Athletic CEOs : leadership in turbulent times - Shekshni͡a, S. V. (Stanislav Vladimirovich); Ulanovsky, Alexey; Zagieva, Veronika (Anthem Press, 2019)
'Athletic CEOs: Leadership in Turbulent Times' presents an unorthodox model of effective business leadership for turbulent environments - Athletic Leadership. Athletic CEOs are not humble or empathic; their leadership is grounded in a combination of toughness and adaptability. They deliver superior performance and transform their companies, employees and near-environments by systematically applying a set of meta-practices.